2021
DOI: 10.1089/jwh.2021.0185
|View full text |Cite
|
Sign up to set email alerts
|

Suicidal Risk in Women with Premenstrual Syndrome and Premenstrual Dysphoric Disorder: A Systematic Review and Meta-Analysis

Abstract: Purpose: Women with premenstrual dysphoric disorder (PMDD) and premenstrual syndrome (PMS) experience substantial functional impairment and decreased quality of life. While previous research has highlighted a relationship between premenstrual disturbances and suicide risk, no meta-analysis has been conducted to quantitatively assess the findings. Methods: A systematic review and meta-analysis was conducted by searching the literature in three databases (Pubmed, PsycINFO… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
23
0
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 41 publications
(27 citation statements)
references
References 36 publications
2
23
0
2
Order By: Relevance
“…A recent meta-analysis of data from prior studies with varied methodologies. Affirmed that PMDD and PMS are both associated with increased risk of reporting SI [ 4 ]. The process of isolating dynamic risk factors related to increased vulnerability to suicide is critically important to the implementation of suicide prevention strategies.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…A recent meta-analysis of data from prior studies with varied methodologies. Affirmed that PMDD and PMS are both associated with increased risk of reporting SI [ 4 ]. The process of isolating dynamic risk factors related to increased vulnerability to suicide is critically important to the implementation of suicide prevention strategies.…”
Section: Discussionmentioning
confidence: 99%
“…Epidemiological studies have concluded that the prevalence of premenstrual symptoms causing clinically significant interference or distress may be as high as 13-18% [3] and comparable with other depressive disorders [3]. PMS has been significantly associated with an increase in suicidal ideation (SI) but not suicide attempts in a recent meta-analysis [4]. Premenstrual dysphoric disorder (PMDD), a severe Open Access *Correspondence: kdeligian1@northwell.edu form of PMS with strictly defined criteria codified by the American Psychiatric Association in the Diagnostic and Statistical Manual of Mental Disorders Version 5 [2], has additionally been associated with SI, plans to suicide, and suicide attempts in meta-analyses [4,5].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…PMS causes various symptoms in women, commonly including affective symptoms, behavioral symptoms, and difficulty concentrating, impairing their quality of normal life ( 7 , 8 ). Among them, women with PMS had difficulty in regulating their emotions ( 9 ), such as prominent depression ( 10 ), making them at higher risk of suicidality ( 11 ).…”
Section: Introductionmentioning
confidence: 99%
“…Given that effective symptoms related to PMS and PMDD can make women more prone to suicidal thoughts, plans, and, in severe cases, attempts, this is an issue that needs to be addressed seriously by health professionals (Prasad et al, 2021 ). Women’s health-related quality of life is severely influenced by PMS, interfering with the development of nations by impairing daily activities (Tolossa & Bekele, 2014 ; Direkvand-Moghadam et al, 2014 ).…”
mentioning
confidence: 99%